COVID-19 Research Comparative Outcome looking through Real-World Evidence Vs. Clinical Trials - Hariharan, Niveditha (British Journal of Healthcare and Medical Research, 2022)
Randomized controlled trials (RCTs) are considered the gold standard because of their conventional study design, accurately defined endpoints, and high-quality evidence to define any cause-effect relationships. On the other hand, Real-world Data (RWD) relates to the collection of data pertaining to health status of the patient and/or delivery of routine health care. As the sources of RWD are becoming vast, Real-World Evidence (RWE) studies are gaining increasing attention. RWE can emerge as the backbone for regulatory decision-making in clinical research by providing adequate scientific evidence. A lot of RWE studies have been conducted in COVID-19, where a variety of repurposed drugs have been tested in real-world settings for the treatment and management of COVID-19. The current need is to work on a Hybrid trial methodology combining the most important parts of traditional RCTs and observational study designs to infer the RWE.